The weakest point of cardiac resynchronization therapy: new technologies facing old terminology - Marcantoni, Lina; Pastore, Gianni; Biffi, Mauro; Zanon, Francesco (Frontiers in Cardiovascular Medicine, 2023)
Patients with symptomatic heart failure (HF) and left bundle branch block (LBBB) are currently treated with biventricular pacing (BiV) which has a Class IA recommendation. Given the possibility to re-establish the inter and intra-ventricular synchrony, BiV iscommonly referred to as cardiac resynchronization therapy (CRT) . This wording is widely utilized and over time the terms BiVand CRT have become interchangeable. Conduction system pacing (CSP) is emerging as a valid therapeutic opportunity to obtain CRTrestoring the native conduction via the Purkinje network. Therefore the acronym CRT is no longer synonymous with BiV only but could also refer to CSP. A terminology update is needed to include the resource of CSP to ensure better communication among all the stakeholders involved in managing recipients of cardiac devices and should be a fundamental step in advancing the quality of patient care. Making use of the NBG code to describe the implantable cardiac device would ease such terminology update, since only the first three positions of the five letters NBG code are commonly utilized, while the last two are rarely used.